MANAJEMEN LPP RRI SURAKARTA DALAM MELESTARIKAN PROGRAM SIARAN PEDESAAN - Dian Esti Nurati, Anastasia Oktavioni Hardika Putri, Buddy Riyanto & (Transformasi, 2016)
This research is descriptive - qualitative aims to describe and analyze the management of LPPRRI Surakarta in preserving the Rural Press program. By using interactive analysis , theresults showed that the leadership of LPP RRI Surakarta has authorized the broadcastprogram coordinator countryside to manage their own all the needs and requirements at thetime of production starting from the planning , organizing, directing and give effect to , andsupervision .Key words: Management, press, rural